Pengembangan Video Animasi Menggunakan Aplikasicanva Untuk Meningkatkan Motivasi Belajar Dan Pemahaman Konsep KPK Dan FPB - Novalin, Eva; Mulyawati, Ima (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This study aims to determine the effect of student motivation and understanding of concepts on learning FPB and KPK using the development of animated video media based on the Canva application at SDN Kedaung Kaliangke 10 in early June. The research method used is ADDIE. Media development was validated by 2 media experts, namely lecturers and 1 material expert, namely homeroom teacher. Data collection techniques in the form of validation sheets, questionnaires, pretest and posttest. Expert validation data analysis using a Likert scale. Meanwhile, the data analysis of learning motivation and understanding of concepts used the N-Gain test. The results of media validation with a percentage of 87.34% have a very valid predicate and the results of material expert validation with a percentage of 92.23% which state that the media is feasible to use. Students' learning motivation increased by having a score of 0.35 while students' understanding of mathematical concepts increased by having a score of 0.79. The result of the research is that animated video media using the Canva application is very feasible to use and can increase students' learning motivation and understanding of concepts.